2022
DOI: 10.3390/genes13112103
|View full text |Cite
|
Sign up to set email alerts
|

Potential CRISPR Base Editing Therapeutic Options in a Sorsby Fundus Dystrophy Patient

Abstract: TIMP3 mutations are associated with early-onset macular choroidal neovascularisation for which no treatment currently exists. CRISPR base editing, with its ability to irreversibly correct point mutations by chemical modification of nucleobases at DNA level, may be a therapeutic option. We report a bioinformatic analysis of potential therapeutic options in a patient presenting with Sorsby fundus dystrophy. Genetic testing in a 35-year-old gentleman with bilateral macular choroidal neovascularisation revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In conclusion, the promise of base editing in severe progressive retinal degeneration with congenital retinal abnormalities such as CRB1 lies in its potential to address the underlying genetic mutations responsible for these conditions [67][68][69]. Base editing offers a precise and targeted approach to correcting specific nucleotide changes associated with these disorders, potentially halting or even reversing disease progression at the genetic level.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the promise of base editing in severe progressive retinal degeneration with congenital retinal abnormalities such as CRB1 lies in its potential to address the underlying genetic mutations responsible for these conditions [67][68][69]. Base editing offers a precise and targeted approach to correcting specific nucleotide changes associated with these disorders, potentially halting or even reversing disease progression at the genetic level.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis showed that RAP lesions respond better to anti-VEGF treatment than other neovascular AMD subtypes [9]. Choroidal neovascularization (CNV) has been associated with several IRDs: Stargardt disease, Best vitelliform dystrophy, Sjögren reticular dystrophy, pattern dystrophy, gyrate atrophy, Sorsby fundus dystrophy, and RP [10,11]. In RP, CNV is extremely rare [11], with the majority of case reports describing either classic CNV [12][13][14][15], pachychoroid neovasculopathy [12],…”
Section: Introductionmentioning
confidence: 99%